2009
DOI: 10.1074/jbc.m809395200
|View full text |Cite
|
Sign up to set email alerts
|

The Electron Transfer Pathway of the Na+-pumping NADH:Quinone Oxidoreductase from Vibrio cholerae

Abstract: The Na ؉ -pumping NADH:quinone oxidoreductase (Na ؉ -NQR) is the only respiratory enzyme that operates as a Na ؉ pump. This redox-driven Na ؉ pump is amenable to experimental approaches not available for H ؉ pumps, providing an excellent system for mechanistic studies of ion translocation. An understanding of the internal electron transfer steps and their Na ؉ dependence is an essential prerequisite for such studies. To this end, we analyzed the reduction kinetics of the wild type Na ؉ -NQR, as well as site-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
117
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(123 citation statements)
references
References 24 publications
(41 reference statements)
6
117
0
Order By: Relevance
“…Additionally, the crystallographic model lacks an anticipated tightly bound quinone, which has been reported in the enzyme preparations from different laboratories (4,6,8) and suggested to be located in NqrA on the basis of photoaffinity labeling and NMR studies (7,9). In the crystallographic model, the NqrA subunit includes a deep cavity that is large enough to accommodate a ubiquinone molecule, but the cavity is ϳ20 Å above the predicted membrane surface and the distance between the cavity and the riboflavin in NqrB subunit is too large (Ͼ40 Å) to be consistent with electron transfer during turnover (Fig.…”
Section: Edited By Ruma Banerjeementioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the crystallographic model lacks an anticipated tightly bound quinone, which has been reported in the enzyme preparations from different laboratories (4,6,8) and suggested to be located in NqrA on the basis of photoaffinity labeling and NMR studies (7,9). In the crystallographic model, the NqrA subunit includes a deep cavity that is large enough to accommodate a ubiquinone molecule, but the cavity is ϳ20 Å above the predicted membrane surface and the distance between the cavity and the riboflavin in NqrB subunit is too large (Ͼ40 Å) to be consistent with electron transfer during turnover (Fig.…”
Section: Edited By Ruma Banerjeementioning
confidence: 99%
“…For instance, the spatial distances between several pairs of redox cofactors in the proposed electron transfer pathway are too large to support physiological rates of electron transfer; for example, the edge-toedge distance between the [2Fe-2S] cluster in NqrF and the Fe(Cys) 4 in NqrD (33.4 Å) and between the FMN and the riboflavin cofactor in NqrB (29.3 Å). The fact that electron transfer between these cofactors takes place indicates that the subunits harboring the cofactors undergo large conformational changes during turnover that decrease these spatial gaps (13).Additionally, the crystallographic model lacks an anticipated tightly bound quinone, which has been reported in the enzyme preparations from different laboratories (4,6,8) and suggested to be located in NqrA on the basis of photoaffinity labeling and NMR studies (7,9). In the crystallographic model, the NqrA subunit includes a deep cavity that is large enough to accommodate a ubiquinone molecule, but the cavity is ϳ20 Å above the predicted membrane surface and the distance between the cavity and the riboflavin in NqrB subunit is too large (Ͼ40 Å) to be consistent with electron transfer during turnover (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies carried out by our group with mutants that do not incorporate individual cofactors have shown that electrons move through the enzyme following the pathway: FAD → 2Fe-2S → FMN C → FMN B → Riboflavin ( Fig. 1) (14).…”
Section: Namentioning
confidence: 99%